Multiply by (x-2): (x-1)² = 9/2(x-2)

Expand the brackets: x² -2x +1 = 9/2x - 9

Rearrange into quadratic form: x² -13/2x +10 = 0

Solve: x = 2.5 or 4

---

(y+2)/(y+1) = x

Rewrite the numerator: (y+1+1)/(y+1) = x

Take out the common factor: 1 + 1/(y+1) = x

Get the y term on its own: 1/(y+1) = x-1

Multiply by y+1: 1 = (x-1)(y+1)

Get the y term on its own: 1/(x-1) = y+1

Make y the subject: y = 1/(x-1) -1

]]>how do you so the following rational equation

(x-1)^2 / x-2 = 9 / 2

and also

how do you make y the subject of the formula when

y+2 / y+1 = x

i been trying to solve this all morning!

anyways guys if you can help please

]]>